184 Does Medicaid Cover Artificial Urinary Sphincter Surgeries? A State-by-State Analysis. Issue 1 (1st April 2022) - Loeb, C.; Barnard, J.; Yafi, F.; Schneider, D.
ABSTRACT: Introduction: Artificial urinary sphincter (AUS) placement is the most effective long-term treatment for men with severe stress urinary incontinence (SUI), typically due to post-prostatectomy intrinsic sphincter deficiency. Published success rates range from 59 to 90 percent and the procedure is associated with very high patient satisfaction. Existing literature regarding insurance coverage and physician reimbursement overwhelmingly focuses on Medicare and commercial plans, leaving a knowledge gap with respect to the Medicaid population, which may contribute to inequitable utilization of this treatment modality for SUI. Objective: To quantify Medicaid coverage for AUS placement and revision for male SUI by state. Methods: State Medicaid websites were utilized to access publicly available physician fee schedules. Individual search queries were performed for CPT codes 53444, 53445, 53446, and 53447, which represent insertion of tandem cuff, insertion of inflatable urethral/bladder neck sphincter, removal of inflatable urethral/bladder neck sphincter, and removal and replacement inflatable urethral/bladder neck sphincter. Data were recorded for each device, including the coverage status and physician fees. Results: Medicaid physician fee schedules were accessible for 49 out of 50 US states. All 49 of these states reported coverage for removal with and without revision of the AUS, 48 states reported coverage for insertion of an AUS, and 48 states reported coverage for insertion of a tandem cuff. Means and range of physician reimbursement for each AUS related procedure were 1, 007.59 (181.84-10, 960.90) for insertion of tandem cuff (53444), 1, 087.40 (199.89-11, 949.86) for insertion of AUS (53445), 596.93 (146.90-1893.12) for removal of AUS (53446), and 1020.14 (208.55-11, 586.74) for removal and replacement of AUS (53447). Conclusions: AUS related surgeries in the Medicaid population are covered by nearly all states as confirmed by publicly available data. Interestingly, removal with and without replacement of AUS was covered by all 49 states with publicly reported data. Knowledge of Medicaid coverage for AUS related surgery may result in improvement in the utilization of this treatment for male SUI and may improve access to care in the Medicaid population. Disclosure: No